An off-target effect of class A CpG-oligonucleotides on suppressing the cyclic GMP-AMP synthase signaling in fibroblastic reticular cells - Jayakumar, Preethi; Jiang, Ting; Huang, Hai; Deng, Meihong (Frontiers in Pharmacology, 2025)
BackgroundClass A CpG-oligonucleotides (ODNs), a Toll-like receptor 9 (TLR9) agonist, have been applied for treating inflammatory diseases and cancer in preclinical studies and clinical trials. A recent study has reported that class A ODNs can activate the Cyclic GMP-AMP synthase (cGAS) signaling to regulate the inflammatory response in human monocytes. However, it remains unknown whether class A ODNs can activate the cGAS pathways in other cell types, such as fibroblastic reticular cells (FRC), which play critical roles in modulating the immune environments during inflammatory diseases and cancer.MethodsTo understand the role of class A ODN in regulating the cGAS signaling in FRC, we treated mouse FRC and human fibroblast with class A ODN, a cGAS agonist (HT-DNA), and combined class A and HT-DNA.ResultsUnexpectedly, we found that class A ODNs suppress the cGAS level and downstream signaling in human and murine FRC. The class A ODN-induced suppression effect on cGAS is limited in FRC, but not other immune cell types, and is independent of TLR9. Performing pulldown assay and Mass spectrum, we found that class A ODNs regulate the cGAS level post translationally by interacting with cGAS and ZNF598, an E3 ubiquitin ligase.ConclusionOur data reveal an unrecognized off-target effect of class A ODN on suppressing the cGAS signaling in FRCs, which should be considered when designing class A ODN regimens for inflammatory diseases and cancer.